Environmentally friendly high temperature resistant electrical steel insulating coating and its preparation method and application
By using water-soluble polyimide resin and optimizing its preparation method, combined with a specific combination of diamine, dianhydride and nanocuring agent, the problem that existing electrical steel insulating coatings cannot achieve multiple excellent performances at the same time is solved, and an efficient, environmentally friendly, and high-temperature resistant insulating coatings are achieved.
Patent Information
- Application Number
- CN202411169918.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The existing electrical steel insulating coatings cannot achieve excellent electrical insulation, environmental protection, high temperature resistance, corrosion resistance and adhesion at the same time, and the preparation method is complex and the cost is high.
The preparation method of polyimide resin is optimized by using water-soluble polyimide resin as the main component, and by combining specific diamines, dianhydrides and nanocuring agents, the preparation method of polyimide resin is optimized, including selecting aromatic diamines, fluorodiamines and silicone-containing cyclodiamines as diamines, butane tetracarboxylic dianhydride and 3,3,4,4-benzophenone tetracarboxylic dianhydride as dianhydride, as well as nanobentonite, cerium oxide and lanthanum oxide as nanopowders.
It realizes the insulation stability and corrosion resistance of the coating at high temperatures, and has rapid curing, good adhesion and environmental protection, reducing production costs and complexity.
Smart Images

Figure BDA0005008981480000091 
Figure BDA0005008981480000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrical steel insulating coatings, and more specifically, to an environmentally friendly high-temperature resistant electrical steel insulating coating, a preparation method thereof, and an application thereof. Background Art
[0002] Electrical steel is a key material used in the manufacture of electrical equipment such as motors and transformers. When electrical steel is used for a long time, it will produce certain eddy current losses. In order to avoid this problem, its surface needs to be coated with insulating coating. During use, electrical steel is usually punched into the shape of an iron core, which requires that the insulating coating of electrical steel not only has good insulation properties, but also has good adhesion and weldability. In addition, in order to adapt to the use environment of different types of iron cores, the insulating coating of electrical steel also needs to have good corrosion resistance, high temperature resistance, etc.
[0003] Existing electrical steel insulation coatings are mainly divided into organic coatings, semi-organic coatings and inorganic coatings. Among them, organic coatings have good film-forming properties and punching properties, but their weldability and heat resistance are poor and they are not environmentally friendly; inorganic coatings have good heat resistance, but poor punching properties and adhesion; semi-organic coatings can combine the advantages of organic coatings and inorganic coatings and have broad application prospects, but existing semi-organic coatings often contain chromates, which are toxic substances that are harmful to human health. The adhesion, punching properties, heat resistance and corrosion resistance of semi-organic coatings without chromates are much lower than those of chromate coatings.
[0004] To solve the above problems, the Chinese patent with the authorization announcement number CN105086695B discloses an environmentally friendly high-insulation coating for electrical steel, which is formulated with the following components in mass percentage: 5-20% barium zirconate; 1-10% aluminum phosphate; 5-20% CaFeO3; 5-30% titanium dioxide; 1-10% barium sulfate; 10-30% water-based acrylic emulsion; 1-5% wetting agent, pH regulator and defoamer; balance deionized water; all the above powders have a particle size of ≥1000 mesh. However, the coating thickness of this technical solution is as high as 5μm, which increases the complexity and cost of construction, especially for the coating of complex shapes or small parts, which requires more labor and time, increasing production costs.
[0005] The Chinese patent with publication number CN114381152A discloses an insulating environmentally friendly coating for cold-rolled non-oriented electrical steel, a preparation method and an application thereof, wherein the insulating environmentally friendly coating is composed of the following raw materials in percentage by weight: 35-62% of aluminum dihydrogen phosphate, 0.3-6% of magnesium oxide, 0.6-7.2% of silica sol, 0.1-4.8% of cerium nitrate, 0.5-4.8% of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.3-3.4% of γ-aminopropyltriethoxysilane, 3.1-8.2% of anhydrous ethanol, 3.2-11.9% of polyurethane, and 22-42% of deionized water, and the sum of the contents of the above raw material components is 100%. However, the insulating environmentally friendly coating of the technical solution needs to be coated twice, and the raw materials need to be prepared in batches, resulting in a relatively complicated preparation method. Summary of the invention
[0006] The purpose of the present invention is to provide an environmentally friendly high-temperature resistant electrical steel insulating coating and a preparation method and application thereof, so as to solve the problem that the existing electrical steel insulating coating cannot achieve excellent electrical insulation, environmental protection, high temperature resistance, corrosion resistance and adhesion. Moreover, the environmentally friendly high-temperature resistant electrical steel insulating coating of the present invention has the advantages of fast curing speed and simple preparation method.
[0007] To achieve the above-mentioned object, the first aspect of the present invention provides an environmentally friendly high temperature resistant electrical steel insulating coating, wherein the raw materials include, by mass percentage: 50-60% of a water-soluble polyimide resin, 8-12% of a nano curing agent, 2-5% of an accelerator, and water supplementing the balance to 100%;
[0008] The raw materials for preparing the water-soluble polyimide include, by weight: 10-15 parts of diamine, 20-30 parts of dianhydride, 50-70 parts of solvent, 25-35 parts of nitrogen-containing alkaline organic compound, and 10-20 parts of dehydrating agent;
[0009] The diamines include aromatic diamines, fluorine-containing diamines and silicon-ester ring-containing diamines, and the mass ratio of the three is (10-15): (1-3): (4-6).
[0010] The inventors have found that when the diamines include aromatic diamines, fluorinated diamines and silicon-containing ester ring diamines, the water-soluble polyimide resin obtained for preparing the coating has good insulation properties while having good heat resistance. The inventors speculate that it is because under the synergistic effect of aromatic diamines, fluorinated diamines and silicon-containing ester ring diamines, the heat resistance of the polyimide resin caused by the thermal degradation of the Si-C bond in the organosilicon structural unit in the polyimide resin can be avoided. At the same time, the flexible segment makes the free volume of the water-soluble polyimide larger, the number of polar groups per unit volume is small, and the dielectric constant of the water-soluble polyimide is small. Further, the inventors have found that when the diamines include aromatic diamines, fluorinated diamines and silicon-containing ester ring diamines, and the mass ratio of the three is (10-15): (1-3): (4-6), the interaction force between the polyimide and the water molecules can be avoided to be weakened due to the hydrophobic groups in the polyimide structure, thereby avoiding the instability of the coating. The inventors speculate that at this mass ratio, the presence of the flexible chain segment makes the free volume of the polyimide structure larger, and water molecules can more easily enter the polyimide molecular chain, thereby improving the solubility of the polyimide, so that the polyimide resin can be evenly dispersed in water.
[0011] Preferably, the aromatic diamine includes at least one of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (p-PD), m-phenylenediamine (m-PDA), o-phenylenediamine, 4,4'-diaminodiphenylmethane (MDA), and 4,4'-bis(4-aminophenoxy)diphenyl sulfone (BAPS).
[0012] More preferably, the aromatic diamine is ODA.
[0013] Preferably, the fluorine-modified diamine includes at least one of 2,2′-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2′-bis(trifluoromethyl)-4,4′-diaminobiphenyl, and 2,2′-bis(trifluoromethyl)-4,4′-diaminophenyl ether.
[0014] More preferably, the fluorine-modified diamine includes 2,2′-bis[4-(4-aminophenoxybenzene)]hexafluoropropane and 2,2′-bis(trifluoromethyl)-4,4′-diaminophenyl ether, and the mass ratio of the two is (1-3):(1-3).
[0015] Preferably, the silicon-ester-containing cyclic diamine includes at least one of bis(4-aminophenoxy)dimethylsilane and 1,3-diaminophenyltetramethyldisiloxane pyromellitic dianhydride.
[0016] More preferably, the silicon-containing ester cyclic diamine is [4-(p-phenoxy)-phenoxy]dimethylsilane.
[0017] Preferably, the dianhydride includes at least one of ethylene tetracarboxylic dianhydride, butane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, cyclopentane diacid dianhydride, cyclohexane tricarboxylic anhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,4,5-1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-1,2,4,5-cyclohexane tetracarboxylic dianhydride, and 3,3,4,4-dibenzophenone tetracarboxylic dianhydride.
[0018] More preferably, the dianhydride comprises butanetetracarboxylic dianhydride and 3,3,4,4-benzophenonetetracarboxylic dianhydride, and the mass ratio of the two is 1:(2-3).
[0019] The inventors have found that even though the heat resistance of polyimide is improved by the synergistic effect of aromatic diamine, fluorine-containing diamine and silicon ester cyclic diamine in a mass ratio of (10-15): (1-3): (4-6), the insulation stability and corrosion resistance of the coating at high temperature are not as good as those of the system containing fillers. In the experimental process, the inventors creatively found that when a specific dianhydride is used, that is, the dianhydride includes butane tetracarboxylic acid dianhydride and 3,3,4,4-dibenzophenone tetracarboxylic acid dianhydride, the above problems can be solved. The inventors speculate that this is because: the intermolecular force of the polyimide formed by butane tetracarboxylic acid dianhydride and 3,3,4,4-dibenzophenone tetracarboxylic acid dianhydride and diamine is large enough, and the molecular chain has suitable rigidity. The coating film after curing can be sufficient to resist the erosion of corrosive substances and the problem of chemical bond breakage or change in molecular chain arrangement caused by high temperature, thereby improving the corrosion resistance and insulation stability of the coating at high temperature.
[0020] Preferably, the organic solvent includes at least one of N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.
[0021] Preferably, the nitrogen-containing basic organic compound includes 2,4-lutidine and 2-(4-aminophenyl)-5-aminobenzimidazole; the mass ratio of the two is (4-6):1.
[0022] The inventors have found that when the nitrogen-containing basic organic compound includes 2,4-lutidine and 2-(4-aminophenyl)-5-aminobenzimidazole, the water solubility of the polyimide is improved while avoiding the decrease in the high temperature resistance of the coating. The inventors speculate that this is because the synergistic effect of the two can avoid the decrease in the molecular chain interaction caused by the inhibition of the close stacking of the molecular chains, thereby reducing the high temperature resistance of the coating, and at the same time, it makes it easier for water molecules to enter the polyimide molecular chain, thereby improving the water solubility.
[0023] Preferably, the dehydrating agent comprises at least one of benzoic anhydride, acetic anhydride, propionic anhydride and butyric anhydride.
[0024] Preferably, the preparation method of the water-soluble polyimide resin comprises the following steps:
[0025] S1. Under nitrogen protection, dissolving diamine in an organic solvent, then adding dianhydride, and stirring to obtain a polyamic acid solution;
[0026] S2, adding a nitrogen-containing basic organic compound to the polyamic acid solution, stirring to obtain a polyimide intermediate;
[0027] S3. Add a dehydrating agent to the polyimide intermediate and heat the mixture to obtain polyimide.
[0028] Preferably, the stirring temperature in step S1 is 25-30° C., and the stirring time is 4-6 h.
[0029] Preferably, the stirring temperature in step S2 is 25-30° C., and the stirring time is 2-4 h.
[0030] Preferably, the temperature of the heating reaction in step S3 is 60-70° C., and the heating reaction time is 1-3 h.
[0031] Preferably, the raw materials of the nano curing agent include, by weight: 60-70 parts of polyisocyanate, 4-8 parts of nano powder, 20-30 parts of N,N-dimethylformamide, and 0.01-0.05 parts of dibutyltin laurate.
[0032] Preferably, the nano powder comprises nano bentonite, cerium oxide and lanthanum oxide, and the mass ratio of the three is (6-10): (1-2): (1-2).
[0033] The inventor unexpectedly discovered that when the nano powder includes nano bentonite, cerium oxide and lanthanum oxide, the prepared nano curing agent and the water-soluble polyimide resin are cured to obtain a coating film having a faster curing speed at room temperature and good adhesion, and avoiding the coating film from peeling off or pulverizing under the condition of annealing and heat preservation at 750°C for 2h. The inventor speculates that it is because the nano powder has a certain volume and surface effect, and the unique valence electron structure of the rare earth oxide makes it easier for the curing agent to cure with the water-soluble polyimide resin, and at the same time, it can be evenly dispersed in the water-soluble polyimide resin, and the flexibility of the coating film is improved by dissipating stress destruction.
[0034] Preferably, the polyisocyanate includes at least one of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,4,4-trimethyl-hexamethylene diisocyanate, preferably 1,6-hexamethylene diisocyanate.
[0035] Preferably, the preparation method of the nano curing agent comprises the following steps: placing the nano powder in N,N-dimethylformamide, adding dibutyltin laurate, adding isocyanate dropwise at 90-100° C. to react for 40-60 min, centrifugally filtering, and drying to obtain the curing agent.
[0036] Preferably, the promoter is an organic metal catalyst, and the organic metal catalyst includes at least one of stannous octoate, stannous isooctanoate and dibutyltin dilaurate.
[0037] The second aspect of the present invention provides a method for preparing an environmentally friendly high temperature resistant electrical steel insulating coating, comprising the following steps: uniformly mixing a water-soluble polyimide resin, a nano curing agent, a accelerator and water to obtain the coating.
[0038] The third aspect of the present invention provides the use of environmentally friendly high temperature resistant electrical steel insulating coating in electrical steel.
[0039] Beneficial effects:
[0040] 1. In the present invention, when the diamine includes aromatic diamine, fluorine-containing diamine and silicon ester ring diamine, the obtained water-soluble polyimide resin is used to prepare a coating having good heat resistance and good insulation performance.
[0041] 2. When the diamines of the present invention include aromatic diamines, fluorine-containing diamines and silicon ester ring diamines, and the mass ratio of the three is (10-15): (1-3): (4-6), the weakening of the interaction force between the polyimide and the water molecules due to the hydrophobic groups in the polyimide structure can be avoided, thereby avoiding the instability of the coating.
[0042] 3. When the present invention uses a specific dianhydride, that is, the dianhydride includes butanetetracarboxylic dianhydride and 3,3,4,4-benzophenonetetracarboxylic dianhydride, and the mass ratio of the two is 1:(2-3), the insulation stability and corrosion resistance of the coating at high temperature are improved.
[0043] 4. In the present invention, when the nitrogen-containing basic organic compound includes 2,4-lutidine and 2-(4-aminophenyl)-5-aminobenzimidazole, the water solubility of the polyimide is improved while the high temperature resistance of the coating is prevented from decreasing.
[0044] 5. When the nano powder of the present invention includes nano bentonite, cerium oxide and lanthanum oxide, the coating obtained after the prepared nano curing agent and the water-soluble polyimide resin are cured has a faster curing speed at room temperature and good adhesion, thereby avoiding peeling or powdering of the coating during the punching process. DETAILED DESCRIPTION
[0045] In order to better explain the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the examples in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other implementation methods obtained by those skilled in the art without making creative work are within the scope of protection of the present invention. The experimental methods in the following embodiments, unless otherwise specified, are conventional methods, and the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can be obtained from commercial channels.
[0046] Example 1
[0047] Environmentally friendly high temperature resistant electrical steel insulating coating, the raw materials include, by mass percentage: 50% water-soluble polyimide resin, 8% nano curing agent, 2% accelerator, and water to make up the balance to 100%;
[0048] The raw materials for preparing the water-soluble polyimide include, by mass, 12 parts of diamine, 25 parts of dianhydride, 60 parts of solvent, 30 parts of nitrogen-containing alkaline organic compound, and 15 parts of dehydrating agent;
[0049] The diamines include aromatic diamines, fluorine-containing diamines and silicon ester ring-containing diamines, and the mass ratio of the three is 12:2:5.
[0050] The aromatic diamine is ODA (CAS No.: 101-80-4).
[0051] The fluorine-modified diamine includes 2,2'-bis[4-(4-aminophenoxybenzene)]hexafluoropropane (CAS No.: 69563-88-8) and 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether (CAS No.: 344-48-9), and the mass ratio of the two is 1:2.
[0052] The silicon-containing ester cyclic diamine is bis(4-aminophenoxy)dimethylsilane (CAS No.: 1223-16-1).
[0053] The dianhydride includes butanetetracarboxylic dianhydride (CAS No.: 4534-73-0) and 3,3,4,4-benzophenonetetracarboxylic dianhydride (CAS No.: 2421-28-5), and the mass ratio of the two is 1:2.
[0054] The organic solvent is N,N-dimethylformamide (CAS No.: 68-12-2).
[0055] The nitrogen-containing alkaline organic compound includes 2,4-lutidine (CAS No.: 108-47-4) and 2-(4-aminophenyl)-5-aminobenzimidazole (CAS No.: 7621-86-5); the mass ratio of the two is 5:1.
[0056] The dehydrating agent is benzoic anhydride (CAS No.: 93-97-0).
[0057] The preparation method of the water-soluble polyimide resin comprises the following steps:
[0058] S1. Under nitrogen protection, dissolving diamine in an organic solvent, then adding dianhydride, and stirring to obtain a polyamic acid solution;
[0059] S2, adding a nitrogen-containing basic organic compound to the polyamic acid solution, stirring to obtain a polyimide intermediate;
[0060] S3. Add a dehydrating agent to the polyimide intermediate and heat the mixture to obtain polyimide.
[0061] The stirring temperature in step S1 is 25° C. and the stirring time is 5 h.
[0062] The stirring temperature in step S2 is 25° C. and the stirring time is 3 h.
[0063] The temperature of the heating reaction in step S3 is 65° C., and the heating reaction time is 2 h.
[0064] The nano curing agent comprises, by weight, 65 parts of polyisocyanate, 5 parts of nano powder, 25 parts of N,N-dimethylformamide, and 0.02 parts of dibutyltin laurate (CAS No.: 77-58-7).
[0065] The nano powder comprises nano bentonite, cerium oxide and lanthanum oxide, and the mass ratio of the three is 8:1:1.
[0066] Nano-bentonite was purchased from Dongguan Ruiheng Mineral Products Co., Ltd.; cerium oxide and lanthanum oxide were both purchased from Beijing Zhongke Keyou Technology Co., Ltd., with a particle size of 20 nm.
[0067] The polyisocyanate is 1,6-hexamethylene diisocyanate (CAS No.: 822-06-0).
[0068] The preparation method of the nano curing agent comprises the following steps: placing nano powder in N,N-dimethylformamide, adding dibutyltin laurate, dropping isocyanate at 95°C for reaction for 50 minutes, centrifugally filtering, and drying to obtain the nano curing agent.
[0069] The promoter is an organic metal catalyst, and the organic metal catalyst is dibutyltin dilaurate.
[0070] The method for preparing an environmentally friendly high-temperature resistant electrical steel insulating coating comprises the following steps: uniformly mixing a water-soluble polyimide resin, a nano curing agent, an accelerator and water to obtain the coating.
[0071] Example 2
[0072] The difference from Example 1 is that the environmentally friendly high-temperature resistant electrical steel insulating coating comprises, by mass percentage, 60% water-soluble polyimide resin, 12% nano curing agent, 5% accelerator, and water to make up the balance to 100%; the rest are the same.
[0073] Example 3
[0074] The difference from Example 1 is that the environmentally friendly high-temperature resistant electrical steel insulating coating comprises, by mass percentage, 55% water-soluble polyimide resin, 10% nano curing agent, 3% accelerator, and water to make up the balance to 100%; the rest are the same.
[0075] Comparative Example 1
[0076] The difference from Example 3 is that the diamine includes an aromatic diamine and a fluorine-containing diamine, and the mass ratio of the three is 12:7, and the rest are the same.
[0077] Comparative Example 2
[0078] The difference from Example 3 is that the diamine includes an aromatic diamine and a silicon ester ring diamine, and the mass ratio of the two is 12:7, and the rest is the same.
[0079] Comparative Example 3
[0080] The difference from Example 3 is that the diamine includes aromatic diamine, fluorine-containing diamine and silicon ester ring diamine, and the mass ratio of the three is 8:5:3, and the rest are the same.
[0081] Comparative Example 4
[0082] The difference from Example 3 is that the dianhydride is butanetetracarboxylic dianhydride, and the rest is the same.
[0083] Comparative Example 5
[0084] The difference from Example 3 is that the dianhydride is 3,3,4,4-benzophenonetetracarboxylic dianhydride, and the rest is the same.
[0085] Comparative Example 6
[0086] The difference from Example 3 is that 3,3,4,4-benzophenonetetracarboxylic dianhydride is replaced by 1,2,4,5-cyclohexanetetracarboxylic dianhydride (CAS No.: 2754-41-8), and the rest are the same.
[0087] Comparative Example 7
[0088] The difference from Example 3 is that the nitrogen-containing basic organic compound is 2-(4-aminophenyl)-5-aminobenzimidazole, and the rest are the same.
[0089] Comparative Example 8
[0090] The difference from Example 3 is that 2,4-lutidine is replaced by triethylamine, and the rest are the same.
[0091] Comparative Example 9
[0092] The difference from Example 3 is that the nano powder is nano bentonite, and the rest is the same.
[0093] Comparative Example 10
[0094] The difference from Example 3 is that cerium oxide is replaced by anhydrous cerium chloride purchased from Inner Mongolia Zhongke Mengxi New Materials Co., Ltd., and the rest is the same.
[0095] Application Examples 1-3 and Comparative Application Examples 1-10:
[0096] The environmentally friendly high temperature resistant electrical steel insulating coatings of Examples 1-3 and Comparative Examples 1-10 were respectively coated on the surface of the steel plate with a coating thickness of 1 μm and cured at 100° C. for 3 seconds.
[0097] Performance Testing:
[0098] 1. Stability: The environmentally friendly high temperature resistant electrical steel insulating coatings of Examples 1-3 and Comparative Examples 1-10 were placed at 25°C for 24 hours to observe whether precipitation occurred. If precipitation occurred, it was unqualified. The results are shown in Table 1.
[0099] 2. The steel plates of Example 1-3 and Comparative Application Example 1-10 were subjected to the following performance tests:
[0100] (1) Insulation and adhesion: Refer to the standard GB / T 2522-2017 Test method for insulation resistance and adhesion of coating on electrical steel strip (sheet);
[0101] (2) Insulation stability: After aging at 450°C for 100 h, the insulation resistance is tested in accordance with the standard GB / T 2522-2017 Test method for insulation resistance and adhesion of coating on electrical steel strip (sheet);
[0102] (3) Corrosion resistance: Refer to the standard GB / T 10125-2012 artificial atmosphere corrosion test salt spray test; use 5% NaCl solution and store it in 35℃ salt spray conditions for 8h; observe whether corrosion occurs. If so, it is recorded as unqualified;
[0103] (4) Heat resistance: After annealing at 750°C for 2 hours under 100% nitrogen protection, observe whether the coating film shows any signs of falling off or powdering. If either of these occurs, the coating is unqualified.
[0104] Test results:
[0105] Table 1 Stability test results of environmentally friendly high temperature resistant electrical steel insulating coatings of Examples 1-3 and Comparative Examples 1-10
[0106] stability Example 1 qualified Example 2 qualified Example 3 qualified Comparative Example 1 Failure Comparative Example 2 Failure Comparative Example 3 Failure Comparative Example 4 qualified Comparative Example 5 qualified Comparative Example 6 qualified Comparative Example 7 Failure Comparative Example 8 Failure Comparative Example 9 qualified Comparative Example 10 qualified
[0107] It can be seen from Table 1 that the stability of the environmentally friendly high-temperature resistant electrical steel insulating coating obtained in Comparative Examples 1-3 is unqualified due to the change in the composition of the diamine, and in Comparative Examples 7-8 is unqualified due to the change in the composition of the nitrogen-containing alkaline organic compound.
[0108] Table 2 Test results of insulation, adhesion, corrosion resistance, heat resistance and weldability of steel plates of application examples 1-3 and comparative application examples 1-10
[0109]
[0110]
[0111] It can be seen from Table 2 that when the environmentally friendly high temperature resistant electrical steel insulating coatings of Examples 1-3 of the present invention are applied to steel plates, the curing speed is fast and the interlayer resistance is as high as 2483-2518Ω·mm 2 / 0.5μm, the interlayer resistance after aging at 450℃ for 100h is still as high as 2348-2433Ω·mm 2 / 0.5μm, and has excellent adhesion, corrosion resistance and heat resistance.
[0112] However, since the composition of the diamine was changed in Comparative Examples 1-3, the interlayer resistance of the corresponding comparative application examples decreased significantly, the heat resistance was unqualified, and the insulation stability and adhesion were also affected.
[0113] Since the composition of dianhydride in Comparative Examples 4-6 was changed, the insulation stability of the corresponding comparative application examples was significantly reduced, and the corrosion resistance and heat resistance were unqualified.
[0114] Since the composition of the nitrogen-containing alkaline organic compound was changed in Comparative Example 7-8, the heat resistance of the corresponding comparative application example was unqualified.
[0115] Since the composition of the nanopowder was changed in Comparative Examples 9-10, the adhesion of the corresponding comparative application examples was significantly reduced and the heat resistance was unqualified.
[0116] The above description is only a specific embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation made by the present invention, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.
Claims
1. Environmentally friendly high temperature resistant electrical steel insulating coating, characterized in that: Calculated by mass percentage, the raw materials include: 50-60% water-soluble polyimide resin, 8-12% nano curing agent, 2-5% accelerator, and water to make up the balance to 100%; The raw materials for preparing the water-soluble polyimide include, by weight: 10-15 parts of diamine, 20-30 parts of dianhydride, 50-70 parts of solvent, 25-35 parts of nitrogen-containing alkaline organic compound, and 10-20 parts of dehydrating agent; The diamine comprises an aromatic diamine, a fluorine-containing diamine and a silicon ester ring-containing diamine, and the mass ratio of the three is (10-15): (1-3): (4-6); The dianhydride comprises butanetetracarboxylic dianhydride and 3,3,4,4-benzophenonetetracarboxylic dianhydride, and the mass ratio of the two is 1:(2-3); The nitrogen-containing alkaline organic compound includes 2,4-lutidine and 2-(4-aminophenyl)-5-aminobenzimidazole; the mass ratio of the two is (4-6):1; The nano curing agent comprises, by weight, 60-70 parts of polyisocyanate, 4-8 parts of nano powder, 20-30 parts of N,N-dimethylformamide, and 0.01-0.05 parts of dibutyltin laurate; The nano powder comprises nano bentonite, cerium oxide and lanthanum oxide, and the mass ratio of the three is (6-10): (1-2): (1-2).
2. The environmentally friendly high temperature resistant electrical steel insulating coating according to claim 1 is characterized in that: The polyisocyanate includes at least one of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,4,4-trimethyl-hexamethylene diisocyanate.
3. The environmentally friendly high temperature resistant electrical steel insulating coating according to claim 1, characterized in that: The promoter is an organic metal catalyst, and the organic metal catalyst includes at least one of stannous octoate, stannous isooctanoate and dibutyltin dilaurate.
4. A method for preparing the environmentally friendly high temperature resistant electrical steel insulating coating according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: uniformly mixing water-soluble polyimide resin, nano curing agent, accelerator and water.
5. Use of the environmentally friendly high temperature resistant electrical steel insulating coating according to any one of claims 1 to 3 in electrical steel.
Citation Information
Patent Citations
A kind of environmental protection high insulation coating for electrical steel
CN105086695B
Insulating environment-friendly coating for cold-rolled non-oriented electrical steel as well as preparation method and application of insulating environment-friendly coating
CN114381152A
High-temperature-resistant waterproof polyimide material and preparation method thereof
CN114672021A
Cathode electrophoretic coating as well as preparation method and application thereof
CN117624958A
Polyimide with high silicon content as well as preparation method and application thereof
CN118373991A